Back-to-basics. Cough: causes and diagnosis - David A. Tibbutt (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
Cough is a common complaint and may be a feature of serious underlying disease. A working knowledge of the mechanisms and differential diagnoses is crucial. A carefully taken clinical history followed by a thorough physical examination will often lead to a correct conclusion and confirmatory investigations and in turn to appropriate management.